A preliminary analysis of the EAW programme: looking from the teachers’ perspective - Md Zamin, Ainul Azmin; Mohd Effendi @ Ewan Mohd Matore2, Mohd Effendi (UiTM Press, 2019)
The objective of this study was to explore the lecturers’ perception of the English for Academic Writing programme by taking into account the aspects of course outline, instructors’ readiness, course materials and course duration. English for academic writing is not only a prerequisite for graduation requirement but it also helps to prepare the students in completing every assignment and task within their study period. While an academic review is important for every course offered at the higher institutions, opinions and voice from all stakeholders including the instructors must be considered. The need to evaluate the curriculum is necessary to determine the effectiveness of the syllabus and its content. This quantitative study explored the opinions’ of teachers who were responsible in delivering the syllabus for the undergraduates at an international university where English is the main medium of instruction. Questionnaires were distributed to 41 instructors at the university’s main campus. Their responses were crucial indicators to elicit information on the effectiveness of the course conducted.Although teachers might evince interest in teaching, Some may not be experts in academic writing based on their own academic qualification and their tenure as lecturers. The results showed that the lecturers were positive in terms of course outline, materials and readiness. However, the lecturers’ general perception for course duration was considered as moderate and there is no significant difference of perception across different personal background. The analysis and discussions from the study provided a platform for curriculum designers to polish and further improve the English for academic writing course.